Akibat Hukum Pelanggaran Hak Cipta Dalam Perspektif Fatwa Majelis Ulama Indonesia Nomor 1 Tahun 2003 Tentang Hak Cipta - Wati Rahmi Ria; Amara Yovitasari (KRTHA BHAYANGKARA, 2022)
One of the fatwa’s issued by the Indonesian Hak Council (MUI) is Fatwa Number 1 concerning Copyright. The community, especially Muslims in Indonesia, certainly needs an explanation of the MUI Fatwa, especially those related to the legal consequences of copyright infringement. Therefoe, the problem in this research is what are the legal cunsequences of copyright infringement in the perspective of MUI Fatwa Number 1 od 2003.This research uses normative legal research type with descriptive research type. The problem approach in this study uses a normative juridical legal problem approach. The data used in this study, such as primary legal materials, secondary legal materials, and tertiary legal materials were analyzed qualitatively. The results of the research and discussion show that Copyright Regulations in Indonesia are regulated in Law Number 28 of 2014 concerning Copyright and MUI Fatwa Number 1 of 2003 concerning Copyright. The legal consequences of Copyright Violations in the perspective of the MUI Fatwa on Copyrights result in three things, that are for the creator or copyright owner whose copyright is violated, for copyright violators and works whose Copyright is violated.